Prince Caspian the return to Narnia - Lewis, C. S. (Clive Staples) 1898-1963 (Lewis, C. S. 1898-1963. (Clive Stapes) Chronicles of Narnia (HaperCollins (Firm)), 1979)
Four children help Prince Caspian and his army of Talking Beasts to free Narnia from evil.